Electromagnetic wave absorbing film and method for preparing same

A two-dimensional sheet-like multilayer electromagnetic wave absorbing film with a lattice arrangement of absorption units addresses structural limitations in existing materials, enhancing impedance matching and absorption bandwidth, and improving mechanical stability and compatibility.

JP7607888B1Active Publication Date: 2025-01-06SUZHOU BOTAO NEW MATERIALS TECHNOLOGY CO LTD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
JP2024112584
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2023-07-13
Filing Date
2024-07-12
Publication Date
2025-01-06
Estimated Expiration
2044-07-12

AI Technical Summary

Technical Problem

Existing electromagnetic wave absorbing materials lack a rational structure design and effective broadband absorption capabilities, particularly in multilayer configurations, limiting their compatibility with various functional materials and impedance matching.

Method used

A two-dimensional sheet-like multilayer structure incorporating a soft magnetic composite material with a lattice arrangement of absorption units, utilizing a soft magnetic alloy and Al2O3 layers, and a polymer elastomer to enhance impedance matching and absorption properties.

Benefits of technology

The multilayer structure improves impedance matching, increases effective absorption bandwidth, and enhances mechanical stability, while maintaining compatibility with diverse materials, offering improved microwave absorption and corrosion resistance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007607888000001_ABST
    Figure 0007607888000001_ABST
Patent Text Reader

Abstract

The present invention provides an electromagnetic wave absorbing film and a preparation method thereof, which can effectively improve the matching between the impedance of the electromagnetic wave absorbing film and the free space impedance through a regularly arranged structural design, thereby increasing the effective absorption bandwidth. [Solution] The electromagnetic wave absorbing film comprises a substrate 1 and an electromagnetic wave absorbing layer 2 provided on the substrate and including a matrix 21 and electromagnetic wave absorbing units 22. The plurality of electromagnetic wave absorbing units are arranged in a lattice pattern within the matrix, and the electromagnetic wave absorbing layer is made of a soft magnetic composite material and a polymer elastomer, the mass fraction of the soft magnetic composite material in the electromagnetic wave absorbing layer is in the range of 10 to 80%, and the plurality of absorbing units arranged in a lattice pattern within the matrix is ​​used.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to the technical field of electromagnetic wave absorbing materials, in particular to an electromagnetic wave absorbing film and a method for preparing the same. [Background technology]

[0002] Electromagnetic shielding and electromagnetic absorbing materials are commonly used to eliminate electromagnetic interference and protect against electromagnetic radiation. Compared with electromagnetic shielding technology, using electromagnetic absorbing materials is the most effective way to eliminate electromagnetic interference. Electromagnetic absorbing materials can absorb most of the electromagnetic waves irradiated on their surface, convert them into heat energy or other forms of energy, and dissipate them, and have already been widely used in cutting-edge technologies such as aviation, medical radiation safety, microwave processing technology, and self-driving cars.

[0003] The absorption characteristics of electromagnetic wave absorbing materials depend on their impedance matching and attenuation characteristics. When the impedance matching is good and the attenuation characteristics are strong, the reflection of electromagnetic waves is low, the dissipation power of electromagnetic waves incident on the electromagnetic wave absorbing material is high, and the absorption characteristics are good. Electromagnetic wave absorbing materials are generally classified into resistive types (e.g., SiC and graphite), dielectric types (e.g., BaTiO 3 , BiFeO 3 ), magnetic and dielectric types (e.g. ferrite, FeSiAl), etc. Compared to other electromagnetic wave absorbing materials, soft magnetic materials have advantages such as high magnetic permeability and magnetic loss, good impedance matching characteristics, and strong absorption characteristics, making them the most practical electromagnetic wave absorbing materials and widely used in the field of communications. Therefore, there is great potential in the development of high-performance soft magnetic materials to be used as electromagnetic wave absorbing materials.

[0004] In addition, in the prior art, most electromagnetic wave absorbing materials are composed of a single-layer absorbing sheet, which is formed by combining an electromagnetic wave absorbing material with a matrix to provide a certain thickness and achieve electromagnetic wave absorbing properties in a specific frequency band. With the diversification of electromagnetic wave absorption scenarios, there is great potential in developing electromagnetic wave absorbing materials with multi-layer broadband radio wave absorbing properties.

[0005] Therefore, the object of the present invention is to provide an electromagnetic wave absorbing film and a preparation method thereof to solve the above technical problems. Summary of the Invention [Problem to be solved by the invention]

[0006] In order to overcome the above shortcomings, the objective of the present invention is to provide a material with a reasonable structure design and a simple preparation method, in which the electromagnetic wave absorbing layer uses a plurality of absorbing units arranged in a lattice pattern in the matrix, and the regularly arranged structure design effectively improves the match between the impedance of the electromagnetic wave absorbing film and the free space impedance, and increases the effective absorption bandwidth, and the soft magnetic alloy composite material is made of soft magnetic alloy, Al, and Al from the inside to the outside. 2 O 3 The present invention aims to provide an electromagnetic wave absorbing film and a preparation method thereof, which use a two-dimensional sheet-like multilayer structure including a soft magnetic alloy layer and an amorphous carbon layer, and which has good properties that can be used with a variety of functional materials compared to a single-layer soft magnetic alloy, and which is expected to be used in a wide range of applications. [Means for solving the problem]

[0007] The object of the present invention is achieved by the following technical means.

[0008] An electromagnetic wave absorbing film comprising a substrate and an electromagnetic wave absorbing layer provided on the substrate, the electromagnetic wave absorbing layer comprising a matrix and electromagnetic wave absorbing units, a plurality of the electromagnetic wave absorbing units being arranged in a lattice pattern within the matrix, the electromagnetic wave absorbing layer being made of a soft magnetic composite material and a polymer elastomer, and the mass fraction of the soft magnetic composite material in the electromagnetic wave absorbing layer being in the range of 10 to 80%.

[0009] The electromagnetic wave absorbing film of the present invention has a rational structural design, and the electromagnetic wave absorbing layer uses a plurality of absorbing units arranged in a lattice pattern within a matrix. The regularly arranged structural design can effectively improve the match between the impedance of the electromagnetic wave absorbing film and the free space impedance, and increase the effective absorption bandwidth.

[0010] The soft magnetic composite material has high saturation magnetic induction strength and low coercive force, and can effectively isolate electromagnetic interference and magnetic field interference. The polymer elastomer acts as a filler and binder in the electromagnetic wave absorbing layer, and the soft magnetic composite material is uniformly dispersed in the electromagnetic wave absorbing layer, thereby improving the electromagnetic wave absorption effect. The soft magnetic composite material and the polymer elastomer are tightly bonded to increase the mechanical strength and stability of the electromagnetic wave absorbing layer.

[0011] Moreover, in the above-mentioned electromagnetic-wave-absorbing film, the soft magnetic composite material is a powder, the powder has a thickness of 0.5 to 1.5 μm and a particle size D50 of 30 to 100 μm.

[0012] In the above electromagnetic wave absorbing film, the soft magnetic composite material is made of a soft magnetic alloy, Al 2 O 3 The amorphous carbon layer is a two-dimensional sheet-like multilayer structure.

[0013] Soft magnetic alloys have the advantages of low magnetocrystalline anisotropy constant and high magnetic permeability, but at the same time, they have the disadvantages of high dielectric constant and poor impedance matching. Therefore, in order to obtain better electromagnetic wave absorption properties, the present invention optimizes the soft magnetic alloy, and the soft magnetic alloy composite material is made of soft magnetic alloy, Al, and Al. 2 O 3 The soft magnetic alloy is a two-dimensional sheet-like multilayer structure including an Al layer and an amorphous carbon layer. Compared with a single-layer soft magnetic alloy, the multilayer structure has good properties that allow it to be compatible with various functional materials, and it has the effect of achieving impedance matching by adjusting the dielectric constant, permeability, and rich interface structure, thereby increasing loss. 2 O3 The provision of the layers not only prevents the generation of carbon nanomaterials on the surface of the soft magnetic composite material, but also introduces multiple scattering and reflection mechanisms to improve the microwave absorption properties; at the same time, this multi-layer structure also provides shielding protection and improves the corrosion resistance of the soft magnetic composite material.

[0014] In the above-mentioned electromagnetic-wave-absorbing film, the soft magnetic alloy is at least one selected from the group consisting of an iron-silicon-aluminum soft magnetic alloy, an iron-silicon soft magnetic alloy, an iron-nickel soft magnetic alloy, an iron-nickel-molybdenum soft magnetic alloy, an iron-aluminum soft magnetic alloy, an iron-silicon-aluminum-nickel soft magnetic alloy, an iron-chromium soft magnetic alloy, and an iron-cobalt soft magnetic alloy.

[0015] Preferably, the soft magnetic alloy is an iron-silicon-aluminium soft magnetic alloy, also known as Sendust alloy, with the main components being Fe9.6-Si5.4-Al.

[0016] In the above electromagnetic wave absorbing film, the substrate is at least one of a PET film, a PI film, a PP film, a PEI film, a polyether ether ketone, a phenolic resin, a PE film, a PC film, a PS film, and a PVC film, the thickness of the substrate is 10 to 300 μm, and the thickness of the electromagnetic wave absorbing layer is 0.1 to 2 mm.

[0017] In the electromagnetic-wave-absorbing film, the polymer elastomer is at least one of polyurethane, acrylic acid, organosilicon, and epoxy resin.

[0018] The present invention also relates to a method for preparing the electromagnetic-wave-absorbing film described above, comprising the following steps S1 to S5: S1: A step of uniformly mixing a soft magnetic composite material and a polymer elastomer to obtain a first mixture; S2: Add the first mixture into a stirrer, then add a solvent, mix the first mixture and the solvent in a mass ratio of 1-5:1-5, and stir thoroughly until homogenous to obtain a second mixture; S3: A process in which the second mixture is applied onto a substrate, spread evenly over the substrate with a scraper, and then placed for 1 to 10 minutes on an acrylic plate having multiple cylindrical permanent magnets arranged in a lattice with their north poles facing upwards, followed by heating, solidification, and molding to obtain an electromagnetic wave absorbing film.

[0019] The soft magnetic composite material has high magnetic induction strength due to multiple cylindrical permanent magnets with their north poles facing upwards in a lattice arrangement arranged on an acrylic plate. Under the action of the magnetic field of the cylindrical permanent magnets, they approach in the approaching direction and come together based on the lattice arrangement of the cylindrical permanent magnets to form multiple electromagnetic wave absorbing units. Based on the upward magnetic direction of the north poles of the cylindrical permanent magnets, the soft magnetic composite material of the multiple electromagnetic wave absorbing units is not interfered with by adjacent magnets, and a stable shape can be obtained.

[0020] In addition, in the above-mentioned preparation method of the electromagnetic-wave-absorbing film, the electromagnetic-wave-absorbing powder is a soft magnetic composite material, and the preparation method includes the following steps S1 to S2: S1: Mix ammonium formate solution, soft magnetic alloy powder, and aluminum sulfate, and disperse ultrasonically for 10 to 3 minutes to obtain a mixed solution. The mixed solution is heated in a water bath at 75 to 85 °C, and is reacted while being kept at that temperature for 1 to 2 hours while stirring. After washing with ethanol several times and magnetic separation, it is dried in an oven at 40 to 50 °C for 1 to 3 days, and then annealed at 350 to 450 °C for 2 hours to obtain Al 2 O 3 obtaining a soft magnetic alloy powder coated with a layer; and S2: Al 2 O 3 The soft magnetic alloy powder coated with the layer is spread evenly on a quartz boat, then placed in a CVD rotary tubular furnace, and heated to 400°C at 3-6°C / min under an argon protective atmosphere with a gas flow rate of 50-100mL / min. Then, acetylene gas is introduced at a flow rate of 20-30mL / min to react for 0.5-1 hour. After the reaction is completed, the acetylene gas is stopped, the material is slowly cooled to 25°C, and taken out to obtain a soft magnetic composite material.

[0021] First, Al is applied to the surface of the soft magnetic alloy powder by the sol-gel method. 2 O 3layer, and then introduce an amorphous carbon layer on the surface of the soft magnetic alloy by CCDV method, the highly resistive amorphous carbon layer can reduce the dielectric constant of the magnetic metal, achieve good impedance matching between the absorbing material and free space, and improve the microwave absorption properties. Effect of the Invention

[0022] Compared with the prior art, the present invention has the following advantageous effects: (1) The electromagnetic wave absorbing film disclosed by the present invention has a reasonable structural design, and the electromagnetic wave absorbing layer uses a plurality of absorbing units arranged in a lattice pattern in the matrix, and the regularly arranged structural design can effectively improve the matching between the impedance of the electromagnetic wave absorbing film and the free space impedance, and increase the effective absorption bandwidth. The electromagnetic wave absorbing layer is made of a soft magnetic composite material and a polymer elastomer, and the soft magnetic composite material has high saturation magnetic induction strength and low coercive force, and can effectively isolate electromagnetic interference and magnetic field interference. The soft magnetic composite material and the polymer elastomer are tightly bonded to increase the mechanical strength and stability of the electromagnetic wave absorbing layer. (2) The electromagnetic wave absorbing film disclosed by the present invention is a composite material of a soft magnetic alloy, and is made of a soft magnetic alloy, Al, and a 2 O 3 The soft magnetic alloy is a two-dimensional sheet-like multilayer structure including an Al layer and an amorphous carbon layer. Compared with a single-layer soft magnetic alloy, the multilayer structure has good properties that allow it to be compatible with various functional materials, and it has the effect of achieving impedance matching by adjusting the dielectric constant, permeability, and rich interface structure, thereby increasing loss. 2 O 3 The layer not only prevents the generation of carbon nanomaterials on the surface of the soft magnetic composite material, but also introduces a multiple scattering and reflection mechanism to improve the microwave absorption properties. At the same time, this multi-layer structure acts as a shielding protection and improves the corrosion resistance of the soft magnetic composite material. (3) The preparation method of the electromagnetic wave absorbing film disclosed by the present invention has a reasonable preparation process, is simple and controllable, and is highly flexible. A plurality of cylindrical permanent magnets with their north poles facing upwards are arranged in a lattice on an acrylic plate to form a plurality of electromagnetic wave absorbing units based on the lattice arrangement of cylindrical permanent magnets. Due to the upward magnetic direction of the north poles of the cylindrical permanent magnets, the soft magnetic composite materials of the plurality of electromagnetic wave absorbing units are not interfered with by adjacent magnets, and a stable shape can be obtained. [Brief description of the drawings]

[0023] [Figure 1] 1 is a schematic cross-sectional view of an electromagnetic-wave-absorbing film according to the present invention. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0024] Hereinafter, the technical means in the embodiments of the present invention will be described clearly and in detail with reference to Comparative Example 1, Example 1, Comparative Example 2, Example 2, specific test data, and Figure 1, but it goes without saying that the described embodiments are only some of the embodiments of the present invention and do not include all of the embodiments. All other embodiments obtained by those skilled in the art on the basis of the embodiments of the present invention without any creative activity are all within the scope of protection of the present invention.

[0025] The raw materials used in Comparative Example 1, Example 1, Comparative Example 2, and Example 2 are all commercially available raw materials commonly used in industry.

[0026] In Comparative Example 1 and Example 1, electromagnetic wave absorbing materials were provided.

[0027] Comparative Example 1 Comparative Example 1 is a sendust alloy, the main components of which are Fe9.6-Si5.4-Al.

[0028] Example 1 Example 1 is a soft magnetic composite material, and the preparation method is as follows: 12.612 g of ammonium formate powder is added to 1 L of deionized water solution, and after dispersion, formic acid solution is added to adjust the pH to 4.4 to obtain an ammonium formate solution; the ammonium formate solution, soft magnetic alloy powder, and aluminum sulfate are mixed in a mass ratio of 506:6:3, and ultrasonically dispersed for 15 minutes to obtain a mixed solution; the mixed solution is heated to 75°C in a water bath, kept at that temperature, and reacted with stirring for 1.5 hours; washed multiple times with ethanol and magnetically separated, then dried in an oven at 45°C for 23 days, and then annealed at 380°C for 2 hours to obtain an Al 2 O 3 The soft magnetic alloy powder coated with the Al layer was obtained. 2 O 3 The soft magnetic alloy powder covered with the layer was spread evenly on a quartz boat, then placed in a CVD rotary tubular furnace, and heated to 400°C at 5°C / min under an argon protective atmosphere with a gas flow rate of 50 to 100 mL / min. Then, acetylene gas was introduced at a flow rate of 25 mL / min to react for 1 hour to produce an amorphous carbon layer. After the reaction was completed, the acetylene gas was stopped and the material was slowly cooled to 25°C and taken out to obtain the soft magnetic composite material of Example 1.

[0029] Measurement of electromagnetic wave absorption characteristics: The electromagnetic parameters of the sendust alloy of Comparative Example 1 and the soft magnetic composite material of Example 1 were measured. The measuring device was a vector analyzer, and the measurement frequency band was 0.5 to 18 GHz.

[0030] For the measurements, the Sendust alloy of Comparative Example 1 and the soft magnetic composite material of Example 1 were made into a coaxial ring, i.e., paraffin, the Sendust alloy of Comparative Example 1, and the soft magnetic composite material of Example 1 were thoroughly mixed in a mass ratio of 1:1 until homogeneous, and a coaxial ring with a thickness of approximately 2.5 mm, an inner diameter of approximately 3.0 mm, and an outer diameter of approximately 7.0 mm was produced.

[0031] Measurement results of electromagnetic wave absorption properties: Generally speaking, when RL<-10 dB, the material is considered to have an effective electromagnetic wave absorption bandwidth. In the frequency range of 0.5-18.0 GHz, the RL value of the sendust alloy of Comparative Example 1 is less than -10 dB in a bandwidth of less than 0.2 GHz, which indicates that the sendust alloy of Comparative Example 1 has a large limit in practical use. The soft magnetic composite material of Example 2 has an RLmin of -23.9 dB at 6.8 GHz, and the effective electromagnetic wave absorption bandwidth can reach 3.4 GHz.

[0032] The measurement results of the electromagnetic wave absorption properties mentioned above were first 2 O 3 The two-dimensional sheet-like multilayer structure of the soft magnetic composite material synthesized by coating a layer of amorphous carbon by the sol-gel method and then coating the amorphous carbon layer by the CCDV method has significantly improved minimum microwave loss value RLmin and effective bandwidth, etc., compared with the two-dimensional sheet-like single-layer structure of the Sendust alloy in Comparative Example 1, which shows that the electromagnetic wave absorption properties of the electromagnetic wave absorbing powder have been greatly improved.

[0033] Comparative Example 2 and Example 2 provide an electromagnetic wave-absorbing film and a preparation method thereof.

[0034] Comparative Example 2 As shown in FIG. 1 , the electromagnetic-wave-absorbing film of Comparative Example 2 includes a substrate 1 and an electromagnetic-wave-absorbing layer 2 provided on the substrate 1. The electromagnetic-wave-absorbing layer 2 uses the sendust alloy and polyurethane of Comparative Example 1. The preparation method of the electromagnetic-wave-absorbing film includes the following steps: S1: A process of uniformly mixing sendust alloy and polyurethane to obtain a first mixture having a mass ratio of sendust alloy powder to polyurethane of 70:30. S2: Add the first mixture into a mixer, then add the solvent methyl isopropyl ketone, mix the solvent methyl isopropyl ketone and the first mixture in a mass ratio of 1:1, and stir thoroughly until homogeneous to obtain a second mixture; S3: A process in which the second mixture is applied onto a PET film (substrate 1), spread evenly over the surface of the PET film with a scraper, and then placed for 6 minutes on an acrylic plate having a plurality of cylindrical permanent magnets (height 2 mm, diameter 2 mm, spacing 6 mm) arranged in a lattice arrangement with their north poles facing upwards and with a residual magnetic flux density of 1 T, followed by heating, solidification and molding to form an electromagnetic wave absorbing layer 2, thereby obtaining an electromagnetic wave absorbing film of Comparative Example 2 in which the PET film is 100 μm thick and the electromagnetic wave absorbing layer 2 is 1 mm thick.

[0035] The electromagnetic-wave-absorbing film of Comparative Example 2 was cut to a size of 300×300 mm, and then its electromagnetic-wave absorption characteristics were measured. The measuring device was a vector analyzer, and the measurement frequency band was 1 to 40 GHz.

[0036] Measurement results of electromagnetic wave absorption properties: At 18GHz, RLmin was -20.1dB, and the effective electromagnetic wave absorption bandwidth could reach 7.9GHz.

[0037] Example 2 As shown in FIG. 1 , the electromagnetic-wave-absorbing film of Example 2 includes a substrate 1 and an electromagnetic-wave-absorbing layer 2 provided on the substrate 1. The electromagnetic-wave-absorbing layer 2 is made of the soft magnetic composite material of Example 1, i.e., polyurethane. The preparation method of the electromagnetic-wave-absorbing film includes the following steps: S1: uniformly mixing the soft magnetic composite material and polyurethane to obtain a first mixture in which the mass ratio of the soft magnetic composite material to the polyurethane is 70:30. S2: Add the first mixture into a mixer, then add the solvent methyl isopropyl ketone, mix the solvent methyl isopropyl ketone and the first mixture in a mass ratio of 1:1, and stir thoroughly until homogeneous to obtain a second mixture; S3: A process in which the second mixture is applied onto a PET film (substrate 1), and then uniformly spread over the surface of the PET film with a scraper. The mixture is then placed for 6 minutes on an acrylic plate having a plurality of cylindrical permanent magnets (height 2 mm, diameter 2 mm, spacing 6 mm) arranged in a lattice arrangement with their north poles facing upwards and each having a residual magnetic flux density of 1 T, followed by heating, solidification and molding to form an electromagnetic wave absorbing layer 2, thereby obtaining the electromagnetic wave absorbing film of Example 2 having a PET film thickness of 100 μm and an electromagnetic wave absorbing layer 2 thickness of 1 mm.

[0038] The electromagnetic-wave-absorbing film of Example 2 was cut into a size of 300×300 mm, and then its electromagnetic-wave absorption characteristics were measured. The measuring device was a vector analyzer, and the measurement frequency band was 1 to 40 GHz.

[0039] Measurement results of electromagnetic wave absorption properties: At 23 GHz, RLmin was -32.3 dB, and the effective electromagnetic wave absorption bandwidth could reach 15.1 GHz.

[0040] The present invention has many specific applications, and the above are only preferred embodiments of the present invention. It should be noted that the above examples are only used to interpret the present invention, and are not intended to limit the scope of protection of the present invention. Those skilled in the art can make some improvements without departing from the principle of the present invention, and these improvements should also be considered as the scope of protection of the present invention. [Explanation of symbols]

[0041] 1 Base material 2. Electromagnetic wave absorbing layer 21. Matrix 22 Electromagnetic wave absorbing unit

Claims

1. A method for producing an electromagnetic wave-absorbing film, comprising the steps of: the electromagnetic wave absorbing film comprises a substrate (1) and an electromagnetic wave absorbing layer (2) provided on the substrate (1); the electromagnetic wave absorbing layer (2) comprises a matrix (21) and electromagnetic wave absorbing units (22), a plurality of the electromagnetic wave absorbing units (22) are arranged in a lattice pattern inside the matrix (21); the electromagnetic wave absorbing layer (2) is made of a soft magnetic composite material and a polymer elastomer, and a mass fraction of the soft magnetic composite material in the electromagnetic wave absorbing layer (2) is in the range of 10 to 80%; The method for preparing the electromagnetic wave-absorbing film includes the steps of: A step S1 of uniformly mixing the soft magnetic composite material and the polymer elastomer to obtain a first mixture; A step S2 of adding the first mixture into a stirrer, then adding a solvent, mixing the first mixture and the solvent in a mass ratio of 1 to 5:1 to 5, and stirring sufficiently until homogenous to obtain a second mixture; and a step S3 of applying the second mixture onto the substrate (1), spreading it evenly over the substrate (1) with a scraper, and then placing the mixture for 1 to 10 minutes on an acrylic plate provided with a plurality of cylindrical permanent magnets arranged in a lattice arrangement with their north poles facing upwards, and then heating, solidifying and shaping the mixture to obtain the electromagnetic wave absorbing film, The method for preparing the soft magnetic composite material comprises the steps of: Ammonium formate solution, soft magnetic alloy powder, and aluminum sulfate are mixed and ultrasonically dispersed for 10 to 3 minutes to obtain a mixed solution, the mixed solution is heated in a water bath at 75 to 85°C, and is reacted while being kept at that temperature for 1 to 2 hours while being stirred. After washing with ethanol several times and magnetic separation, it is dried in an oven at 40 to 50°C for 1 to 3 days, and then annealed at 350 to 450°C for 2 hours to obtain Al. 2 O 3 A step S1 of obtaining a soft magnetic alloy powder coated with a layer; A 2 O 3 The soft magnetic alloy powder coated with the layer is spread evenly on a quartz boat, then placed in a CVD rotary tubular furnace, heated to 400° C. at 3-6° C. / min under an argon protective atmosphere with a gas flow rate of 50-100 mL / min, and then reacted for 0.5-1 hour by introducing acetylene gas at a flow rate of 20-30 mL / min. After the reaction is completed, the acetylene gas is stopped, the powder is slowly cooled to 25° C., and the powder is taken out to obtain the soft magnetic composite material. A method for producing an electromagnetic wave-absorbing film, comprising:

2. 2. The method for producing an electromagnetic-wave-absorbing film according to claim 1, characterized in that the soft magnetic composite material is a powder, the powder has a thickness of 0.5 to 1.5 μm, and the powder has a particle size D50 in the range of 30 to 100 μm.

3. The soft magnetic composite material is made of a soft magnetic alloy from the inside to the outside. 2 O 3 3. The method for producing an electromagnetic-wave-absorbing film according to claim 2, characterized in that the film has a two-dimensional sheet-like multilayer structure including a carbon layer, an amorphous carbon layer, and an amorphous carbon layer.

4. 4. The method for producing an electromagnetic-wave-absorbing film according to claim 3, wherein the soft magnetic alloy is at least one selected from the group consisting of an iron-silicon-aluminum soft magnetic alloy, an iron-silicon soft magnetic alloy, an iron-nickel soft magnetic alloy, an iron-nickel-molybdenum soft magnetic alloy, an iron-aluminum soft magnetic alloy, an iron-silicon-aluminum-nickel soft magnetic alloy, an iron-chromium soft magnetic alloy, and an iron-cobalt soft magnetic alloy.

5. 2. The method for producing an electromagnetic-wave absorbing film according to claim 1, characterized in that the base material (1) is at least one of a PET film, a PI film, a PP film, a PEI film, a polyether ether ketone, a phenolic resin, a PE film, a PC film, a PS film, and a PVC film, the thickness of the base material (1) is 10 to 300 μm, and the thickness of the electromagnetic-wave absorbing layer (2) is 0.1 to 2 mm.

6. The method for producing an electromagnetic-wave-absorbing film according to claim 1 , wherein the polymer elastomer is at least one of polyurethane, acrylic acid, organosilicon, and epoxy resin.

Citation Information

Patent Citations

  • Novel nanocrystalline composite material and preparation process thereof

    CN106298139A

  • Magnetic wave-absorbing metamaterial and preparation method thereof

    CN114498067A

  • Electromagnetic wave absorbing sheet and manufacturing method therefor

    JP2008198873A